PERACANGAN SISTEM PENDETEKSI BANJIR DAN SISTEM PERINGATAN DINI BERBASIS BOT TELEGRAM - Fajri Razak; Muhammad Syahputra Novelan; Arpan Arpan (Ensiklopedia Education Review, 2022)
A flood is a disaster that is difficult to predict by the community when it will occur, therefore there are many casualties caused by the flood disaster. Information that is difficult to obtain by the community is an obstacle to dealing with current floods. One of them is the lack of monitoring to detect the height of the water surface, making it difficult for people to evacuate themselves. The flood detection sensor monitoring system is a technology that can monitor the height of the water surface waves where the data obtained by the sensor will be sent on a telegram.  Keywords: Flood, Monitoring, Telegram.